1996
DOI: 10.1037/0022-006x.64.5.1044
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone, relapse prevention, and supportive therapy with alcoholics: An analysis of patient treatment matching.

Abstract: Alcohol-dependent patients (N = 97) were randomly assigned to receive either naltrexone or placebo and either relapse prevention therapy or supportive therapy. The present report explored the hypothesis that patients could be matched to the above treatments on the basis of specific pretreatment characteristics. Treatment matching variables explored included craving, alcohol dependence severity, and cognitive measures of learning and memory. Results of linear regression analyses tentatively suggest that patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 31 publications
(67 reference statements)
4
63
1
2
Order By: Relevance
“…Exposure to environmental stimuli associated with drinking (such as pictures, smells, and places of ingestion) can strongly stimulate the 'urge' or desire to consume alcohol in alcohol-dependent individuals. In this context, craving for alcohol can be thought of as a useful target for both counseling and pharmacotherapies aimed at reducing alcoholism (Anton, 1999;Flannery et al, 2001;Jaffe et al, 1996). While it appears that craving is accompanied by changes in regional brain activity, what changes and what structures are most sensitive to cue-induced craving are beginning to be clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to environmental stimuli associated with drinking (such as pictures, smells, and places of ingestion) can strongly stimulate the 'urge' or desire to consume alcohol in alcohol-dependent individuals. In this context, craving for alcohol can be thought of as a useful target for both counseling and pharmacotherapies aimed at reducing alcoholism (Anton, 1999;Flannery et al, 2001;Jaffe et al, 1996). While it appears that craving is accompanied by changes in regional brain activity, what changes and what structures are most sensitive to cue-induced craving are beginning to be clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Furthermore, treatment with naltrexone, an opiate antagonist, decreases ethanol consumption by alcoholic subjects. [47][48][49][50] Opioid content, biosynthesis, and release are altered after alcohol treatment, although there is considerable disagreement regarding the direction of changes in the activity of the endogenous opioid system by alcohol. 46 We recently showed that Huh.8 cells express -opioid receptor and that morphine enhances HCV RNA expression in these cells (Li Y, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of efficacy of naltrexone in some alcohol-dependent patients has led to investigations that focus on questions regarding which patients are most benefited by this treatment. Indeed, some clinical trials have shown family history to be a predictor of treatment response (Jaffe et al, 1996;Monterosso et al, 2001).…”
Section: Introductionmentioning
confidence: 99%